Investigation of Charge Transfer Kinetics of Polyaniline Supercapacitor Electrodes by Scanning Electrochemical Microscopy. Issue 1 (27th May 2014) - Sumboja, Afriyanti; Tefashe, Ushula Mengesha; Wittstock, Gunther; Lee, Pooi See
<x xml:space="preserve">Abstract</x> Scanning Electrochemical Microscopy (SECM) is introduced as a promising technique to probe localized interfacial kinetics at the interface of electrolyte/supercapacitor electrode based on polyaniline (PANI) by measuring approach curves from which heterogeneous charge transfer rate constants (keff) are extracted. The values correlate with the effectiveness of the electrode material for supercapacitor application. Specifically, measurements on PANI films of different thicknesses show that potential‐dependent rate constants are observed only for PANI films of up to 5 μm thickness. In addition to the thickness of PANI, keff is also found to be affected by the applied potential and surface morphology of PANI electrodes. These findings correlate with the macroscopic electrochemical performance of PANI electrodes which shows enhanced specific charge storage ability when their thickness is below 5 μm. Under these conditions, they deliver a specific capacitance of 486 F g−1 and a rate capability of 89%. The observed correlation between microscopic kinetic data determined by SECM and macroscopic device characteristics provides rational guidelines for the optimization of the physical and structural properties of high performance supercapacitor electrodes.